Jumping with control: the interplay between psychological constructs and run-up variability in elite jumpers - Moura, Larissa de Paula; Moura, Nelio Alfano; Moura, Tania Fernandes de Paula; Moura, Túlio Bernardo Macedo Alfano; Brandão, Maria Regina Ferreira (Frontiers in Psychology, 2024)
Objectives The purpose of this study was to examine the relationship between psychological aspects (emotional regulation, self-control, mood states, and perceived stress) and components of run-up variability in horizontal jumps and to conduct comparisons based on sex, events (long jump and triple jump), and contextual situations (training versus competition). Methods A total of 10 elite-level athletes (five males and five females) with a mean age of 27.14 (±4.25) years were recruited for the study. All participants had competed nationally or internationally and had 13.10 (±3.48) years of athletic experience. Data were collected during competitions and training sessions for 5 weeks. The participants completed the Brunel Mood Scale, Emotional Regulation Questionnaire, Brief Self-Control Scale, and Visual Analogical Scale of Perceived Stress before each session. The components of run-up variability of successful and failed attempts were measured using video analysis. Data were analyzed using a t-test, Pearson’s correlation, and Cohen’s d. Results Athletes specializing in long jump and triple jump displayed similar psychological and run-up variability characteristics. However, females showed higher values for tension and depression, whereas males had higher run-up speeds and vigor. In competitions, athletes tended to have higher vigor, lower fatigue and confusion, an earlier beginning of the adjustment phase, fewer failed attempts, and higher run-up speed than during training. Emotional regulation is inversely related to depression in women during competitions, whereas higher self-control is associated with fewer failed jumps. Conclusion Athletes competing in the long jump and the triple jump do not differ in psychological traits and run-up characteristics, which suggests that similar training strategies can be used in both events. However, different solutions should be used considering the sex of athletes, with a particular focus on utilizing emotion regulation tools to modulate depression in female jumpers. It is recommended to include training sessions that simulate competition demands, primarily to ensure the early onset of the run-up adjustment phase.